Determination of patterns of biologically relevant aldehydes in exhaled breath condensate of healthy subjects by liquid chromatography/atmospheric chemical ionization tandem mass spectrometry - Andreoli, Roberta; Manini, Paola; Corradi, Massimo; Mutti, Antonio; Niessen, Wilfried M. A. (Rapid communications in mass spectrometry, 2003)
A method for the simultaneous determination of several classes of aldehydes in exhaled breath condensate (EBC) was developed using liquid chromatography/atmospheric pressure chemical ionization tandem mass spectrometry (LC/APCI‐MS/MS). EBC is a biological matrix obtained by a relatively new, simple and noninvasive technique and provides an indirect assessment of pulmonary status. The measurement of aldehydes in EBC represents a biomarker of the effect of oxidative stress caused by smoke, disease, or strong oxidants like ozone. Malondialdehyde (MDA), acrolein, α,β‐unsaturated hydroxylated aldehydes [namely 4‐hydroxyhexenal (4‐HHE) and 4‐hydroxynonenal (4‐HNE)], and saturated aldehydes (n‐hexanal, n‐heptanal and n‐nonanal) were measured in EBC after derivatization with 2,4‐dinitrophenylhydrazine (DNPH). Atmospheric pressure chemical ionization of the analytes was obtained in positive‐ion mode for MDA, and in negative‐ion mode for acrolein, 4‐HHE, 4‐HNE, and saturated aldehydes. DNPH derivatives were separated on a C18 column using variable proportions of 20 mM aqueous acetic acid and methanol. Linearity was established over 4–5 orders of magnitude and limits of detection were in the 0.3–1.0 nM range. Intra‐day and inter‐day precision were in the 1.3–9.9% range for all the compounds. MDA, acrolein and n‐alkanals were detectable in all EBC samples, whereas the highly reactive 4‐HHE and 4‐HNE were found in only a few samples. Statistically significant higher concentrations of MDA, acrolein and n‐hexanal were found in EBC from smokers. Copyright © 2003 John Wiley & Sons, Ltd.